1976
DOI: 10.1021/bi00660a006
|View full text |Cite
|
Sign up to set email alerts
|

The identity of a cyanogen bromide fragment of bovine dentin collagen containing the site of an intermolecular cross-link

Abstract: A peptide fraction isolated from a cyanogen bromide digest of bovine dentin collagen had a molecular weight of 46000. Its size and amino acid composition indicated that it could not consist of peptides derived from the cleavage of a single alpha chain. On reduction with tritiated sodium borohydride, radioactivity was incorporated primarily into 5, 5'-dihydroxylysinonorleucine without degradation at the peptide backbone. Periodate cleavage of the reduced or nonreduced peptide fraction generated one fragment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Thus it is possible that in bovine corneal collagen too, this peptide is cross-linked and would therefore be eluted in a different position on the CM-cellulose column. Similarly fragment a2-CB4 is joined to peptide al-CB6 in dentin collagen (Scott et al, 1976), giving a cross-link peptide that appears on sodium dodecyl sulphate/polyacrylamide-gel electrophoresis with a relative mobility identical with that of the component with a mobility of 0.33 shown in Fig. 1.…”
Section: Results and Discussion Collagen Type In Corneal Stromamentioning
confidence: 94%
“…Thus it is possible that in bovine corneal collagen too, this peptide is cross-linked and would therefore be eluted in a different position on the CM-cellulose column. Similarly fragment a2-CB4 is joined to peptide al-CB6 in dentin collagen (Scott et al, 1976), giving a cross-link peptide that appears on sodium dodecyl sulphate/polyacrylamide-gel electrophoresis with a relative mobility identical with that of the component with a mobility of 0.33 shown in Fig. 1.…”
Section: Results and Discussion Collagen Type In Corneal Stromamentioning
confidence: 94%
“…At present, it would appear that aldehyde formation is limited to the terminal regions of the molecule in bone and tendon collagen. However, Scott et al (1976) have recently identified a cross-linked fragment from bovine dentin collagen which involves «1-CB6 and «2-CB4. In this fragment, a substantial fraction of the cross-link appears to be derived from the condensation of hydroxyallysine in ct2-CB4, located in the collagen helix.…”
Section: B Distribution In the Collagen Moleculementioning
confidence: 99%
“…Aldimines would result from allysine or hydroxyallysine reaction with amino groups of lysyl or hydroxylysyl residues [28]. Since 3H-dihydroxylysinonorleucine and 3H-hydroxylysinonorleucine are the major and minor tritiated amino acids in acid hydrolysates of reduced bone and dentin collagens, the major and minor reducible cross-links are dehydrohydroxylysino hydroxynorleucine and dehydrohydroxylysinonorleucine, respectively [16,[30][31][32][33]. Since 3H-dihydroxylysinonorleucine and 3H-hydroxylysinonorleucine are the major and minor tritiated amino acids in acid hydrolysates of reduced bone and dentin collagens, the major and minor reducible cross-links are dehydrohydroxylysino hydroxynorleucine and dehydrohydroxylysinonorleucine, respectively [16,[30][31][32][33].…”
Section: Studies On the Nature Gf The Linkage Regionmentioning
confidence: 99%
“…After reduction with aH-borohydride, acid hydrolysis, and chromatography of the acid hydrolysate, every collagenous tissue exhibits a characteristic profile of :~H-containing reduced cross-link amino acids [29,30]. These cross-link components are not destroyed by CNBr digestion in 70% formic acid and have been recovered in their expected concentrations as :~H-dihydroxylysinonorleucine and :~H-hydroxylysinonorleucine among the soluble peptides even when CNBr digestion preceded borohydride reduction [16,30,33]. These cross-link components are not destroyed by CNBr digestion in 70% formic acid and have been recovered in their expected concentrations as :~H-dihydroxylysinonorleucine and :~H-hydroxylysinonorleucine among the soluble peptides even when CNBr digestion preceded borohydride reduction [16,30,33].…”
Section: Studies On the Nature Gf The Linkage Regionmentioning
confidence: 99%
See 1 more Smart Citation